Hubungan Pengetahuan Tentang Anemia, Status Gizi, dan Sosial Ekonomi Pada Kejadian Anemia Pada Ibu Hamil di Wilayah Kerja Puskesmas Gandus Palembang Tahun 2023 - Claudia, Fitri Sindi; Ciselia, Dewi; Afrika, Eka (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
One of the causes of maternal death is iron deficiency anemia in pregnant women which can cause complications in pregnancy. According to the World Health Organization (WHO), in 2021 the prevalence of pregnant women worldwide who experience anemia is 41.8%, the prevalence of anemia in pregnant women in Africa by 57.1%, Asia 48.2%, Europe 25.1% and America 24.1%. The prevalence of anemia in Indonesia in 2019 is 48.9%. Based on data from the South Sumatra Provincial Health Office in 2020 the prevalence of anemia in pregnant women reached 7.26%, while the aim of this study was to determine the relationship between knowledge about anemia, nutritional status and socioeconomic status with the incidence of anemia in pregnant women in the work area of the puskesmas gandus palembang in 2023. Type and Design Research is quantitative in nature using an analytic survey method with a cross sectional approach. The population in this study were all pregnant women who checked at the Gandus Health Center in 2023, totaling 467 people. Samples were taken by accidental sampling technique. The number of respondents used in this study was 34 respondents. The results of univariate analysis obtained from 34 respondents, 6 (17.6%) experienced anemia and 28 respondents (82.4%) did not experience anemia. The results of the chi-square statistical test for knowledge variable obtained ρ value = 0.031, nutritional status variable ρ value = 0.001, socioeconomic variable ρ value = 0.041 less than α = 0.05 indicating that there is a significant relationship between knowledge and the incidence of anemia in pregnant women at the Gandus Health Center in Palembang in 2023. Suggestions for the Gandus Health Center are expected. This research can be used as input material in an effort to increase information to the Gandus Health Center, especially about anemia in pregnant women.